B-type natriuretic peptide for incident atrial fibrillation—The Heinz Nixdorf Recall Study. Issue 6 (June 2015) - Kara, Kaffer; Geisel, Marie Henrike; Möhlenkamp, Stefan; Lehmann, Nils; Kälsch, Hagen; Bauer, Marcus; Neumann, Till; Dragano, Nico; Moebus, Susanne; Jöckel, Karl-Heinz; Erbel, Raimund; Mahabadi, Amir Abbas
Abstract: Background: Atrial fibrillation (AF) is the most common arrhythmia and is associated with increased morbidity and mortality. Thus, identifying subjects with unknown AF or at higher risk for future AF in the general population is of importance. B-type natriuretic peptide (BNP) is linked with silent cardiac diseases. We evaluated the association of BNP with incident AF in a large population-based cohort study. Methods: We included subjects from the population-based Heinz Nixdorf Recall study without known coronary heart disease, prior stroke, history of open heart surgery, heart-device therapy, or prevalent AF at baseline. Association of continuous and binary (≥31 pg/ml for male, ≥45 pg/ml for female) BNP with incident AF after 5 years was assessed using logistic regression analysis. Results: A total of 3067 subjects (mean age 58.9 years, 47.9% male) were included in this analysis. Subjects with incident AF ( n  = 42) had higher levels of BNP (median (Q1; Q3): 33.2 pg/ml (19.4; 50.5) vs. 16.9 pg/ml (9.2; 30.2)). Likewise, BNP was associated with incidence of AF both in univariate model and when adjusting for AF risk factors (odds ratio (OR) (95% confidence interval (CI)): BNP as continuous variable: 1.27 (1.09; 1.47), p  = 0.002; BNP as binary variable: 2.68 (1.41; 5.11) with AF risk factor adjustment). Notably, especially younger subjects (<60 years) showed stronger association with incident AF than older ones (OR (95%CI) for dichotomized BNP: 7.20 (1.60; 32.49), p  = 0.01 for <60 years, vs. 2.13 (0.89; 5.09), p  = 0.09 for 60–70 years, and 4.40 (1.29; 14.97), p  = 0.02 for >70 years). Conclusions: Elevated levels of BNP are associated with significant excess of incident AF, independent of traditional AF risk factors in the general population. Gender-specific BNP thresholds may help in prevention by detecting unknown or future AF, which carries a high risk of stroke events.